Chlorhexidine wipes to reduce multidrug-resistant gram-negative bacterial colonization and healthcare-associated infections among medical inpatients: A cluster-randomized trial - Yong Rongrungruang (2022)
Objective: To evaluate efficacy of chlorhexidine gluconate (CHG) to decolonize multidrug-resistant (MDR) gram-negative bacilli (GNB) bacteria, and to reduce healthcare associated infections (HAIs) in general medical inpatients. Materials and Methods: A 1-year, cluster-randomized study was conducted in a university hospital-based general medical unit. Eligible patients were randomized by study ward for routine daily and extra wiping with non-rinsed CHG-cloths (CHG group, n=145) or rinsed, non-medicated soap bath (control group, n=145), consecutively to the end of study. Study nurses received training and audits per CHG protocol. In all participants, axillae, groins, and perianal area were sampled to detect GNB colonization, on day 4 to 7 and day 11 to 14 of admission, by surveillance culture. All were followed for incidence rates of HAIs to day 14 of the study, or study exclusion. Results: MDR GNB colonization were significantly lower in CHG group than those of control group, both day 4 to 7 (15.9% versus 43.4%, respectively, p<0.01), and day 11 to 14 of admission (20.6% versus 65.4%, respectively, p<0.01). The incidence rates of overall HAIs did not differ between groups (5.80 versus 7.10 episodes per 1,000 patient-day, respectively, p=0.84). Three patients developed minor skin irritation in CHG group. Discussion: To the investigators’ knowledge, the present study is the first to demonstrate significant CHG reduction of MDR GNB colonization among medical patients in non-critical care unit. Use of non-rinsed CHG bath, personnel training, and audits, may maintain adequate skin concentration of CHG, and lower risk of cross-transmission. To effectively reduce HAIs, combined CHG bath and bundle of care may be required. Conclusion: Non-rinsed chlorhexidine baths are safe, well-tolerated, and effective to reduce MDR gram-negative bacterial colonization among general medical inpatients, and possible to lower risk of subsequent HAIs and cross-transmission, by day 14 of admission.